2010
DOI: 10.1007/s00417-010-1378-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surgery and intraocular lens implantation timing on visual outcome in traumatic cataract

Abstract: In traumatic cataract, the visual outcome did not differ between primary and secondary cataract extraction and between primary and secondary IOL implantation in adults. In the amblyogenic age, primary surgery with IOL implantation should be preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 6 publications
(7 reference statements)
1
25
0
2
Order By: Relevance
“…One study recommends that in patients with open-globe trauma, the IOL calculation and implantation should be done in a secondary time, since the refractive results are better than performing the calculation with the contralateral healthy eye [15]. However, in a study by Rumelt, no difference was found in terms of best-corrected visual acuity between primary and secondary IOL implantation [16].…”
Section: Discussionmentioning
confidence: 97%
“…One study recommends that in patients with open-globe trauma, the IOL calculation and implantation should be done in a secondary time, since the refractive results are better than performing the calculation with the contralateral healthy eye [15]. However, in a study by Rumelt, no difference was found in terms of best-corrected visual acuity between primary and secondary IOL implantation [16].…”
Section: Discussionmentioning
confidence: 97%
“…[28][29][30][31][32] These underlying complications of ocular trauma may go unnoticed and untreated until they have progressed severely. 28 given that the physiological pressure of the eye is approximately 15 mmHg (8 in H 2 O) and the water streams resulted in pressures as high at 7006 mmHg (135 psi), it is possible but unknown if chronic eye injuries may result.…”
Section: Discussionmentioning
confidence: 99%
“…27 Traumatic glaucoma and cataracts have been linked with open and closed globe injuries. [28][29][30][31][32] Quantifying intraocular pressure during impacts will provide additional insight to these vision problems. Therefore, the purpose of this study is to quantify injury risk of hyphema, lens dislocation, retinal damage, and globe rupture associated with water jets of common stream sizes with velocities up to 8.5 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,12 El tratamiento quirúrgico con implante de LIO para niños con catarata traumática es efectivo para la rehabilitación visual. 11,13 En Israel, se encontró significancia estadística en cuanto al pobre resultado visual en ojos áfacos comparados con pseudofacos. Treinta y dos pacientes de 54 no completaron un año de seguimiento, lo cual podría deberse a que, en su mayoría, provenían del área rural del país (lejanía de la ciudad capital, difícil acceso a las comunidades, pobreza extrema).…”
Section: Discussionunclassified